FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN DIGITAL BANKING DI KALANGAN GENERASI Z KOTA SURABAYA DENGAN MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL - Sharon Wong; Destya Wiranata; Angelique Jocelyn; Clarissa Amanda Polandauw; Ansella Jovita; Nanik Linawati (MANAJEMEN DEWANTARA, 2025)
The main aim of this study is to investigate the factors that influence the adoption of digital banking within the Generation Z age range, especially factors such as perceived ease of use and perceived usefulness. Thus, this research provides an in-depth insight of how these 2 factors affect one’s desire to adopt digital banking. This study is quantitative, with the use purposive sampling, targeting Generation Z digital banking users in Surabaya city with a sample size of 145 respondents. The data was acquired by creating a questionnaire in Google Form, which is then analyzed by the use of SmartPLS with the utilization of Structural Equation Modelling (SEM) method. The SEM method was used to test the relationship between the independent variables (perceived ease of use and perceived usefulness) and dependent variable (adoption of digital banking). The study’s findings depict that both perceived ease of use and perceived usefulness have significant influence towards Generation Z’s adoption of digital banking.